2017
DOI: 10.3390/geosciences7040119
|View full text |Cite
|
Sign up to set email alerts
|

Wood Petrifaction: A New View of Permineralization and Replacement

Abstract: Petrified wood has traditionally been divided into two categories based on preservation processes: permineralization (where tissues are entombed within a mineral-filled matrix) and replacement (where organic anatomical features have been replicated by inorganic materials). New analytical evidence suggests that for most petrified wood, permineralization and replacement are not independent processes; instead, both processes may occur contemporaneously during diagenesis. Infiltration of mineral-bearing groundwate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
37
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 28 publications
5
37
0
5
Order By: Relevance
“…This opal A → opal CT → quartz transformation sequence is well-documented for the diagenesis of siliceous marine sediments and for siliceous hot spring sinter, but evidence from fossil wood is less clear. This sequence is certainly a possibility for some fossil wood occurrences, but many investigations [24][25][26][27][28] have shown that the fossilization of wood may involve multiple episodes of mineralization, and that quartz may occur as a primary precipitate, akin to the formation of crystalline quartz in veins and geodes.…”
Section: Mineralogymentioning
confidence: 99%
“…This opal A → opal CT → quartz transformation sequence is well-documented for the diagenesis of siliceous marine sediments and for siliceous hot spring sinter, but evidence from fossil wood is less clear. This sequence is certainly a possibility for some fossil wood occurrences, but many investigations [24][25][26][27][28] have shown that the fossilization of wood may involve multiple episodes of mineralization, and that quartz may occur as a primary precipitate, akin to the formation of crystalline quartz in veins and geodes.…”
Section: Mineralogymentioning
confidence: 99%
“…During diagenesis, silica minerals follow an opal-A, opal-CT/C microcrystalline quartz transformation [3]. The process of silification of rocks, silica stabilization in the context of the transition of opal into quartz, and the metasomatic silification of different rocks have all been discussed in the literature [4][5][6], while latest studies relate mainly to fossilized trees [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Replacement occurs when the original organic materials are replicated by inorganic minerals. Recently, Mustoe (2017) argued that these two processes are not independent, but, rather occur contemporaneously. If the alternative material is a silica (silicon dioxide), it is specifically called "silicification."…”
Section: Introductionmentioning
confidence: 99%